Electrochemical detection of bisphenol A by tyrosinase immobilized on electrospun nanofibers decorated with gold nanoparticles. - MERCANTE, L. A. (2021)
Bisphenol A (BPA) is an endocrine-disrupting chemical (EDC) employed in industrial processes that causes adverse effects on the environment and human health. Sensitive and inexpensive methods to detect BPA are therefore needed. In this paper, we describe an electrochemical biosensor for detecting low levels of BPA using polymeric electrospun nanofibers of polyamide 6 (PA6) and poly(allylamine hydrochloride) (PAH) decorated with gold nanoparticles (AuNPs), namely, PA6/PAH@AuNPs, which were deposited onto a fluorine-doped tin oxide (FTO) substrate. The hybrid layer was excellent for the immobilization of tyrosinase (Tyr), which allowed an amperometric detection of BPA with a limit of detection of 0.011 µM in the concentration range from 0.05 to 20 µM. Detection was also possible in real water samples with recoveries in the range of 92–105%. The improved sensing performance is attributed to the combined effect of the large surface area and porosity of PA6/PAH nanofibers, the catalytic activity of AuNPs, and oxidoreductase ability of Tyr. These results prov